A review of endoscopic balloon dilatation techniques for treating Crohn's strictures: time to standardise therapy. (2nd October 2016) - Arebi, Naila; Hart, Ailsa L.; Thomas-Gibson, Siwan
ABSTRACT: Introduction : Endoscopic balloon dilatation (EBD) is a recognised treatment for symptomatic Crohn's disease strictures. Over 3000 procedure are reported in the literature and yet the long term benefits are unclear. This is largely because of different populations, study designs, techniques, types of strictures, the outcome measures used and follow-up periods. Areas covered : We summarised the techniques reported in the literature based on a systematic review and key factors that may influence outcome: pre-intervention imaging, stricture length and type, balloon size in relation to intestinal lumen diameter, duration of dilatation, frequency of repeat dilatation and instructions on follow-up. Expert c ommentary : We noted that shorter, non-ulcerated and anastomotic strictures fare better and 2 mins dilatation duration was the commonest technique used without an increased risk of complications. The findings were translated into a standardised protocol and a management pathway to guide clinicians on the therapeutic strategy for Crohn's strictures. To resolve the uncertainty about long-term benefits, future studies should adopt a replicable standardised EBD technique, define degree of fibrosis to decide therapy accordingly, compare it to alternative interventions (strictureplasty or stents) within a randomised controlled trial and apply a validated outcome measure to include intestinal damage and quality of life.